Influence of NbO₂ and SnO₂ additions on the properties of YBa₂Cu₃Oˍδ bulk superconductor synthesised via thermal treatment method - Mohd Yusuf, Nur Nabilah (2018)
YBa2Cu3O7-δ bulk sample had been synthesized using thermal treatment method. The microstructure and superconducting properties of the sample with the addition of NbO2 and SnO2 were studied. Both additions improve the resistance-temperature, R-T properties with smaller superconducting transition, ΔT compared to pure sample. While alternating current susceptibility, ACS measurement showed degradation of intergranular coupling with enhanced intragranular pinning strength in NbO2 added sample, enhanced coupling is observed in SnO2 added sample. Among the added sample, maximum Josephson current, Io is found to be the highest in 0.8 wt% NbO2 (131.44 μA) and 0.4 wt% SnO2 (664.42 μA) compared to pure sample (146.05 μA). Xray diffraction analysis revealed that NbO2 added sample leads to the formation of YBa2NbO6 phase while SnO2 addition reduces the Y211 secondary phase in the Y123 sample. Y123 phase is found to enhanced with SnO2 addition up to 95.8 % (0.4 wt%) compared to 91.5% in pure sample. The scanning electron microscope, SEM images showed an increase in grain size as both addition increases. Sponge-like grain structures is observed in NbO2 and is randomly distributed across the sample pertained to YBa2NbO6 phase while SnO2 addition causes Sn to precipitate on the surface sample and agglomerates at the grain boundaries. Here, SnO2 addition seems to have the upper hand as the overall current transport in high Tc is governed by the intergranular coupling where weak links is associated.